PERAN FINTECH DALAM MENINGKATKAN KEUANGAN INKLUSIF PADA UKM DI KABUPATEN PAMEKASAN - Purwanto Purwanto; Ach Resa Rachrizi; Isnain Bustaram (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2021)
Financial inclusion in UMKM in the pamekasan district. In this study, researchers took 4 samples randomly, from cooperatives and small and medium enterprise offices. Analysis of the data used in this study was to use data reduction then data presentation and the last was conclusions. The results of the research were that of the four informants as a whole receiving well with the presence of fintech because fintech can facilitate transactions. Fintech also provides many benefits for UMKM as well as more benefits from UMKM. The more efficient and effective business activities that made applied fintech and the development of the era require businesses to use fintech. Of the many advantages of fintech, there were certainly disadvantages, one of which was when the financial technology was problematic, it must be repaired and requires some time. Not only that, human resources that lack mastery of fintech made business people have to provide insight into fintech..